Linguistic incomprehension in British asylum appeal hearings. Issue 2 (April 2016) - Gill, Nick; Rotter, Rebecca; Burridge, Andrew; Allsopp, Jennifer; Griffiths, Melanie
Abstract : For the thousands of appellants who navigate Britain's asylum appeal courts every year, attending a hearing conducted in a language they do not understand and participating via an interpreter, is usually viewed as a significant disadvantage. The findings of a study that entailed ethnographic and structured observations of over 390 asylum appeal hearings in England and Wales during 2013 and 2014, however, indicate that the presence of interpreters often offers an important source of support in adversity. While the natural assumption may be to associate linguistic incomprehension with detriment, it transpires that there are important exceptions to this rule. Given the toughening of UK border controls in recent years, as well as British reluctance to share responsibilities for international refugees such as those fleeing from violence in Syria, these observations offer rare solace in a bleak policy landscape.